2021
DOI: 10.1186/s43055-021-00430-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of uterine artery Doppler in assessment of unexplained infertility

Abstract: Background The study aimed to compare the values of uterine artery Doppler indices including resistance index (RI), pulsatility index (PI), and systolic/diastolic (S/D) ratios in fertile female and female with unexplained infertility and investigate their association with unexplained infertility. This study included 70 women divided into two groups. Study group included 40 women with unexplained infertility and control group included 30 fertile women. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…16,30, 31 A recent comparative study by Zarad et al found significantly higher uterine artery Doppler indices in women with unexplained infertility as compared to fertile women. 16 The mean value of RI and PI was significantly higher in the infertile group as compared to the fertile group. They predicted cut off values of ≥0.67 and 1.95 for RI and PI respectively for increased resistance to uterine blood flow with sensitivity of 95%-100%, specificity of 86.7%-96.7%.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…16,30, 31 A recent comparative study by Zarad et al found significantly higher uterine artery Doppler indices in women with unexplained infertility as compared to fertile women. 16 The mean value of RI and PI was significantly higher in the infertile group as compared to the fertile group. They predicted cut off values of ≥0.67 and 1.95 for RI and PI respectively for increased resistance to uterine blood flow with sensitivity of 95%-100%, specificity of 86.7%-96.7%.…”
Section: Discussionmentioning
confidence: 83%
“…[11][12][13] High impedance to uterine blood flow is associated with unexplained infertility, poor endometrial receptivity and, recurrent miscarriages. [14][15][16] Optimum uterine blood flow is an important contributor to good endometrial receptivity. Studies have been done to compare conception and nonconception cycles of women for the difference in uterine blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…Балльная система оценки хронического эндометрита по ультразвуковым критериям Table 1. Scoring system for chronic endometritis assessment using the ultrasonic criteria стического компонента сосудистой стенки, составляет в норме 0,83 ± 0,06 (М ± SD), показатель систоло-диастолического соотношения не превышает 2,7 ± 0,09 [11,13].…”
Section: материалы и методыunclassified
“…Particularly during pelvic and gynecologic surgery, they have a crucial clinical role in a variety of medical disorders. The uterine arteries undergo significant modifications throughout pregnancy, growing larger and more tortuous, which has a significant impact on postnatal outcomes 1 .…”
Section: Introductionmentioning
confidence: 99%